Success Factors in Creating Consumer Trust of Standardized Herbal Medicine in East Java, Indonesia - Suryadi, Nanang; Suryana, Yuyus; Komaladewi, Rita; Sari, Diana (International Journal of Engineering and Technology, 2018)
The development of Herbal Medicines in various countries of the World has been a discussion of researchers. Indonesia is one of the countries that uses and produces herbal medicine, which is believed to have enormous natural resources to support the development of this plant-based medicine. Consumer Trust becomes an interesting phenomenon to be examined more deeply, because the use of herbal medicine [traditional] is still less by modern medicine [chemical] when consumers buy for their own treatment. Several studies in various contexts show that Perceived Value has an impact on Consumer Trust. Nevertheless whether in the context of herbal medicine consumer perceptions of the value of herbal medicinal products will affect the trust of taking the herbal medicine. This study uses the design of Structural Equational Modeling analysis, and involving 357 respondents. In this article was revealed the influence of dimensions of Perceived Value to Consumer Trust of Herbal Medicines with Emotional Value, Functional Value, and Price Value Significantly Positive effect Consumer Trust, only one dimension has no significant effect that is Social Value.Â